The Implementation of the Research Roadmap and Its Contribution to Lecturers' Scientific Publication Productivity in an Islamic Education Study Program at a Higher Education Institution - Ajat Rukajat; Agus Susilo Saefullah; Muhammad Azdzahaby Al Faraya (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: The Implementation of the Research Roadmap and Its Contribution to Lecturers' Scientific Publication Productivity in an Islamic Education Study Program at a Higher Education InstitutionObjective: This study aims to analyze the implementation of the research roadmap and its contribution to the scientific publication productivity of lecturers in the Islamic Religious Education Study Program. Method: The study utilized a qualitative case study design. Data were collected through semi-structured interviews with the study program coordinator and lecturers, as well as a documentation review of the research roadmap, Internal Quality Audit (AMI) documents, and lecturer publication data. Data were analyzed using the Miles and Huberman interactive model. Results: The research roadmap serves as a strategic instrument for directing and controlling research activities, strengthening the focus of studies, encouraging academic collaboration, and increasing the scientific publication productivity of lecturers as well as student involvement in research. Conclusion: The implementation of the roadmap supports the development of a targeted, collaborative, and sustainable research ecosystem. Contribution: These findings reinforce the concept of research governance through the utilization of a roadmap as an instrument to increase the scientific publication productivity of lecturers.INDONESIAN: Implementasi Roadmap Penelitian dan Kontribusinya terhadap Produktivitas Publikasi Ilmiah Dosen pada Program Studi Pendidikan Agama Islam di Perguruan TinggiTujuan: Penelitian ini bertujuan menganalisis implementasi roadmap penelitian dan kontribusinya terhadap produktivitas publikasi ilmiah dosen pada Program Studi Pendidikan Agama Islam. Metode: Penelitian menggunakan desain studi kasus kualitatif. Data dikumpulkan melalui wawancara semi-terstruktur dengan koordinator program studi dan dosen, serta studi dokumentasi terhadap roadmap penelitian, dokumen Audit Mutu Internal (AMI), dan data publikasi dosen. Data dianalisis menggunakan model interaktif Miles dan Huberman. Hasil: Roadmap penelitian berfungsi sebagai instrumen strategis untuk mengarahkan dan mengendalikan kegiatan penelitian, memperkuat fokus kajian, mendorong kolaborasi akademik, serta meningkatkan produktivitas publikasi ilmiah dosen dan keterlibatan mahasiswa dalam penelitian. Kesimpulan: Implementasi roadmap mendukung pengembangan ekosistem penelitian yang terarah, kolaboratif, dan berkelanjutan. Kontribusi: Temuan ini memperkuat konsep tata kelola penelitian melalui pemanfaatan roadmap sebagai instrumen peningkatan produktivitas publikasi ilmiah dosen.